Androgen Receptor Inhibitors in the Treatment of Acne Vulgaris: Efficacy and Safety Profiles of Clascoterone 1% Cream [Letter] - Mazzetti A; Kyeremateng K; Moro L (Dove Medical Press, 2023)
Alessandro Mazzetti,1 Kizito Kyeremateng,2 Luigi Moro1 1Cassiopea S.p.A., Lainate, Italy; 2Sun Pharmaceutical Industries, Inc., Princeton, NJ, USACorrespondence: Kizito Kyeremateng, Sun Pharmaceutical Industries, Inc, 2 Independence Way, 2nd Floor, Princeton, NJ, 08540, USA, Tel +1 640-230-0831, Email Kizito.kyeremateng@sunpharma.com